Autoimmune Lymphoproliferative Syndrome: A Rare Cause of Disappearing HDL Syndrome. (8th August 2016) - Sriram, Swetha; Joshi, Avni Y.; Rodriguez, Vilmarie; Kumar, Seema
Abstract : The term disappearing HDL syndrome refers to development of severe high density lipoprotein cholesterol (HDL-C) deficiency in noncritically ill patients with previously normal HDL-C and triglyceride levels. Autoimmune lymphoproliferative syndrome (ALPS) is a disorder of the immune system due to an inability to regulate lymphocyte homeostasis resulting in lymphadenopathy and hepatosplenomegaly. We describe a 17-year-old boy who was evaluated in the lipid clinic for history of undetectable or low HDL-C and low density lipoprotein cholesterol (LDL-C) levels. Past medical history was significant for ALPS IA diagnosed at 10 years of age when he presented with bilateral cervical adenopathy. He was known to have a missense mutation in one allele of the FAS protein extracellular domain consistent with ALPS type 1A. HDL-C and LDL-C levels had been undetectable on multiple occasions, though lipids had not been measured prior to the diagnosis of ALPS. He had been receiving sirolimus for immunosuppression. The HDL-C and LDL-C levels correlated with disease activity and improved to normal levels during times when the activity of ALPS was controlled. This case highlights the importance of considering ALPS as a cause of low HDL-C and LDL-C levels in a child with evidence of lymphoproliferation.